THE STUDY OF INTERTEXTUALITY ON NOVEL ENTITLED A VERY YUPPY WEDDING AND DIVORTIARE BY IKA NATASSA - Zahria Farlydia Farikhin (Universitas Airlangga, 2019)
This research aimed to describe intertextual in the novel A Very Yuppy Wedding and Divortiare by Ika Natassa. This research used a descriptive qualitative approach in the form of structural. The result of the data analysis is that theme has similarity. The themes of these novels are love, friendship, and family. Figure and characterization in the novels has less different, the figures describe as a work hard figure not only for the job but also on their relationship. In both of the novel, both of the main characters are women and use the first person as the point of view. Whereas the plot of the novels has different, that is novel Divortiare has a flash-back plot and A Verry Yuppy Wedding has a progressive plot. Both of the novel have differences in the story but have the same happy ending. The background of the stories are not different. Ika Natassa takes both of the settings in Jakarta. The conclusion is both of the novels have no significant differences.